State of the National Security Culture among Young Population in the Republic of Serbia - Bodin, Milenko M.; Radojević, Kristina Z.; Kesić, Dušan B. (Sociološki pregled, 2019)
The subject of this paper is to examine the attitudes held by young population, age 16 to 19, in the Republic of Serbia about certain security issues, with the general aim to identify the state of the national security culture. Theoretical background comprises a systemic overview of definitions and interpretations of the terms “security culture” and “national security culture”. The conducted research was based on the method of a semi-structured questionnaire aiming at covering fundamental elements, including knowledge and attitude of the young generation about security issues in the Republic of Serbia. Results indicate that young people in Serbia consider drugs and corruption as dominant threats, and believe that the police, security services, and private security play a major role in the prevention.
Keywords: national security culture; security culture; young population